Histological component quantification for the evaluation of endometrial receptivity in women with natural cycles undergoing in vitro fertilization/intracytoplasmic sperm injection - Dong-Ying Wang; Li Tian; Danhua Shen; Zhen-Juan Yang (Elsevier, 2017)
Objective: Our aim was to evaluate the value of the volumetric fraction of vascular endothelial cells (EnVF) for determining endometrial receptivity in women undergoing in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI). Materials and methods: The records of women undergoing IVF/ICSI between 2006 and 2010 were retrospectively reviewed. An endometrial biopsy was performed in the cycle prior to IVF/ICSI. EnVF was calculated from endometrial biopsy staining. Results: Twenty-seven patients who did not become pregnant, 8 who had a miscarriage, and 21 with a clinical pregnancy were included. The three groups were similar with respect to infertility and IVF characteristics. An EnVF ≤3.85 was associated with not becoming pregnant, an EnVF >5.29 with miscarriage, and a level between 3.86 and 5.29 was associated with clinical pregnancy (p = 0.001). Conclusions: EnVF examined in the prior cycle may be a marker of endometrial receptivity and predict the chance of pregnancy in women undergoing IVF/ICSI.